2019
DOI: 10.1002/jcp.28364
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of DLEU1 expression by epigenetic modification promotes tumorigenesis in human cancer

Abstract: The function of DLEU1 in human cancer is largely unknown. The Cancer Genome Atlas data were applied to identify the landscape of differential genes between tumor tissues and normal tissues, which was further validated by our cohort data and pan‐cancer data including 33 cancer types with 11,060 patients. Next, DLEU1 was selected to validate the novel finding and result showed that it promoted tumorigenesis in vitro and in vivo. Mechanistically, DLEU1 promotes SRP4 expression via increasing H3K27ac enrichment to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
4
9
0
Order By: Relevance
“…In our study, promoter hypomethylation led to the upregulation of DLEU1 expression in ESCC. In line with our findings, a recent report suggests that decreased DNA methylation and increased histone modifications may contribute to DLEU1 upregulation in cancer [ 46 ]. Drug resistance is the main reason for the failure of chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, promoter hypomethylation led to the upregulation of DLEU1 expression in ESCC. In line with our findings, a recent report suggests that decreased DNA methylation and increased histone modifications may contribute to DLEU1 upregulation in cancer [ 46 ]. Drug resistance is the main reason for the failure of chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…LncRNA DLEU1 predicted a poor prognosis of gastric cancer and promoted cell proliferation through the apparent inhibition of KLF2 ( 18 ). The present study also suggested that the expression of PVT1 and DLEU1 in tumor tissues was notably higher than that in normal tissues ( 18 21 ). A positive regulatory relationship existed between lncRNA DLEU1 and lncRNA PVT1, and the effects of lncRNA DLEU1 and lncRNA PVT1 on gastric adenocarcinoma were similar, both of which were highly expressed in tumor tissues.…”
Section: Discussionsupporting
confidence: 70%
“…COBLL1 is the ancestor of a family of proteins involved in morphogenesis and embryonal patterning in organisms with axial symmetry and is upregulated in castrate-resistant prostate cancer with poor prognosis 37 . Upregulation of DLEU1 can also promote tumorigenesis 38 . A question, therefore, emerges whether excess abdominal fat mediates the development of cancers associated with abdominal obesity 39 , or abdominal obesity and cancer are parallel outcomes with shared genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%